2016
DOI: 10.21527/2237-6453.2016.37.293-327
|View full text |Cite
|
Sign up to set email alerts
|

Empreendedorismo Digital: estudo do Projeto Negócios Digitais desenvolvido pelo SEBRAE-PR em Maringá

Abstract: ResumoFazer negócios no meio digital popularizou-se diante do barateamento da infraestrutura de telecomunicações e nesse ambiente a competitividade torna-se cada vez mais acirrada. Com o intuito de apoiar o micro e pequeno empreendedor durante esse processo, o Sebrae Paraná concebeu o Projeto Negócios Digitais, que posteriormente foi operacionalizado por unidades municipais, como o Sebrae Maringá. Isto posto, o objetivo do presente estudo é compreender como o Projeto Negócios Digitais realizado pelo Sebrae Mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 2 publications
0
11
0
12
Order By: Relevance
“…In addition to these characteristics, the study by Pereira and Bernardo (2016) shows that digital entrepreneurs need to keep up to date and master the technologies they use in their a multicase study in startups. Articles International Journal of Innovation -IJI, São Paulo, 9(2), p. 219-238, May/Aug.…”
Section: Theoretical Foundationmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to these characteristics, the study by Pereira and Bernardo (2016) shows that digital entrepreneurs need to keep up to date and master the technologies they use in their a multicase study in startups. Articles International Journal of Innovation -IJI, São Paulo, 9(2), p. 219-238, May/Aug.…”
Section: Theoretical Foundationmentioning
confidence: 99%
“…The results showed that the current entrepreneur needs to be more qualified, know the business, have a strategic vision, organizational and communication skills, intuition, experience, flexibility, adaptability to change and know how to work in a team. Specifically, the digital entrepreneur, in addition to the characteristics inherent to the current entrepreneur, needs to keep up to date and master the technologies he uses in his business, always being attentive to the needs and desires of his customers, seeking to efficiently satisfy them using information technologies to achieve success (Pereira & Bernardo, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ao se rediscutir o empreendedorismo como fenômeno social e interativo é possível entender que o ator que desenvolve novos negócios é um agente transformador, dialógico e reflexivo, operando sob a inspiração de suas experiências (DENTONI, 2017). Essas experiências são vivenciadas e desenvolvidas também por meios digitais, que vêm se popularizando e tendo seus custos reduzidos a partir de novas plataformas digitais, sendo esse o ambiente o espaço onde se centra a prática empreendedora no campo dos games indie (PEREIRA, 2016).Tal prática promove liberdade de ação em cenários de instabilidade e incerteza, autenticidade na configuração da arquitetura do jogo e aperfeiçoamento na criação visual e artística (NAMBISAN, 2017).…”
Section: Introductionunclassified